2004
DOI: 10.1113/jphysiol.2004.068619
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of tissue oxygen levels in the mammalian lens

Abstract: Opacification of the lens nucleus is a major cause of blindness and is thought to result from oxidation of key cellular components. Thus, long-term preservation of lens clarity may depend on the maintenance of hypoxia in the lens nucleus. We mapped the distribution of dissolved oxygen within isolated bovine lenses and also measured the rate of oxygen consumption (Q O 2 ) by lenses, or parts thereof. To assess the contribution of mitochondrial metabolism to the lens oxygen budget, we tested the effect of mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(140 citation statements)
references
References 53 publications
2
137
0
1
Order By: Relevance
“…The objective to increase oxygenation of the vitreous chamber should be offset by the caveat that increased PO 2 is implicated in the generation of nuclear sclerotic cataracts 10,28 . Therefore, a balance between maintaining sufficient oxygenation to support the viability of surrounding tissues but preventing the development of unwanted side-effects needs to be established.…”
Section: Discussionmentioning
confidence: 99%
“…The objective to increase oxygenation of the vitreous chamber should be offset by the caveat that increased PO 2 is implicated in the generation of nuclear sclerotic cataracts 10,28 . Therefore, a balance between maintaining sufficient oxygenation to support the viability of surrounding tissues but preventing the development of unwanted side-effects needs to be established.…”
Section: Discussionmentioning
confidence: 99%
“…In the vitreous near the posterior of the human lens, the pO 2 drops to approximately 7 mmHg (approx.1% O 2 ) [21] and our recent measurements in human patients revealed that the pO 2 near the anterior and lateral surfaces of the lens is typically about 3 mmHg (less than 0.4%) [22]. The low oxygen near the surfaces of the lens and the consumption of oxygen by lens cells results in even lower pO 2 in the lens nucleus [23,24]. Therefore, cells in the eye are exposed to conditions that, for typical cells, would range from hyperoxic to severely hypoxic.…”
Section: Oxygen Toxicitymentioning
confidence: 99%
“…These cells have no mitochondria, peroxisomes, endoplasmic reticulum, or other organelles known to generate ROS. They are also in a very low-oxygen environment [24,27]. With their high levels of glutathione, superficial fibre cells are probably the least likely cells in the body to suffer oxidative damage.…”
Section: Oxygen Toxicitymentioning
confidence: 99%
“…Perhaps because of its low glutathione concentrations, the lens core is maintained at a very low partial pressure of oxygen (45). Our aggregation reactions were carried out under ambient atmosphere.…”
Section: W42q Aggregation Depends On Formation Of a Non-native Disulfidementioning
confidence: 99%